Proportional mortality patterns among chemical plant workers exposed to formaldehyde. Issue 4 (November 1982) - Marsh, G M
Abstract : To examine the possible health risks associated with occupational exposure to formaldehyde a proportional mortality analysis was conducted on deaths occurring between 1950 and 1976 among 136 men who had been employed a month or more in one of five formaldehyde-related areas of a large chemical producing plant located in Springfield, Massachusetts, USA. Overall, no statistically significant excesses or deficits in proportional mortality were observed among the formaldehyde-exposed group based on comparisons with both United States men and men from the local county area. In addition, no important differences in mortality were observed among this group when comparisons were made with 456 male decedents from the same plant who had not had a month or more of formaldehyde exposure. Within the calendar period examined, no deaths from sinonasal cancer were observed among the chemical workers studied nor was mention made on any death certificate of sinonasal cancer as a contributory cause of death. No important excesses, trends, or patterns in cancer mortality were observed among white male formadelhyde-exposed workers when consideration was given to age and time period of death, type and duration of formaldehyde exposure, and the lapse period from the onset of the first formaldehyde-related job assignment. Although certain limitations of this study do not allow definite conclusions to be drawn, the results indicate no trends or patterns in proportional mortality that could be directly linked to exposures to formaldehyde.